Marketing de fidelización de clientes para mejorar el posicionamiento de la empresa ECU WORLDWIDE, ciudad de Guayaquil - Insuaste Suárez, Diana Paola (2019)
The titling work developed in this document is called "Customer Loyalty Marketing to improve the positioning of the company ECU WORLDWIDE, city of Guayaquil", in which it is proposed by means of strategies, to increase the level of satisfaction of the clients of the company and therefore, generate the loyalty of these. The company ECU WORLDWIDE is dedicated to the management of activities within the logistics field, going through several problems related to the low level of loyalty in its customer base, causing it to lose positioning, both locally and internationally…......